Said Hawwa and Modern Tasawuf: An Introduction - Rudiawan Sitorus; Hasyimsyah Hasyimsyah; Abrar M. Dawud Faza (Budapest International Research and Critics University, 2022)
Returning to the focus of this study, Said Hawwa drew the author to introduce his thoughts on the discussion of modern Tasawuf. In the field of Tasawuf, Said Hawwa studied with Tasawuf figures of his time, such as Sheikh Muhammad al-Hasyimi as the head of the tariqah ad-Darqawiyyah in Damascus, then he also studied with Sheikh Ibrahim al-Ghalayini, the leader of the tariqah an-Naqsyabandiyyah, even he follows the halaqah of this tarekat remembrance. But then he did not continue because this new teacher told him to 'uzlah. The approach used is a sociological approach, by maintaining the social conditions that influence the character's thinking when he is in his country of Syria under the auspices of the eastern tradition and the Arab world of thought where he is in the midst of a society that adheres to modernization, secularization and globalization. In addition, it also uses a historical approach, to see the background of the character's thoughts, previous figures that influenced his thinking, as well as in the spiritual aspect in the history of the development of science in each tradition and religion.